2008
DOI: 10.1111/j.1540-8159.2008.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life in Brazilian Pacemaker Patients

Abstract: In this first systematic study of QoL in a Latin American pacemaker population, AQUAREL detected well-impaired health-related QoL scores in different groups of patients, particularly in those with Chagas disease. Heart failure, evaluated by functional class, was the strongest predictor of low QoL in pacemaker patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
3
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
3
22
3
5
Order By: Relevance
“…Therefore, this study also showed a direct relationship of functional class, which reflects the degree of heart failure, quality of life in patients with pacemakers, confirming reports by other authors, such as Stofmeel et al [18] Oliveira et al [8,23]; Cunha et al [9].…”
Section: Quality Of Life X Functional Classificationsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, this study also showed a direct relationship of functional class, which reflects the degree of heart failure, quality of life in patients with pacemakers, confirming reports by other authors, such as Stofmeel et al [18] Oliveira et al [8,23]; Cunha et al [9].…”
Section: Quality Of Life X Functional Classificationsupporting
confidence: 80%
“…Oliveira et al [23] studied quality of life in 139 patients with pacemakers, identified relationship between poorer quality of life related to health in patients with pacemakers with Chagas disease, female gender, unmarried status and the worst functional class. In multivariate analysis, the worst functional class stood out as an independent predictor of poor quality of life related to health in the physical component of the SF-36 and in all domains of AQUAREL.…”
Section: Quality Of Life X Functional Classificationmentioning
confidence: 99%
“…Thus, higher scores represent a worse HRQoL. Another instrument, the Assessment of QUAlity of life and RELated events (AQUAREL) is a specifi c questionnaire for evaluating HRQoL in pacemaker patients (27) and was used in one study (28) .…”
Section: Resultsmentioning
confidence: 99%
“…One showed that the presence of ChD was not associated with SF-36 scores although the patients (n = 92, aged 65.3 ± 12.4 years) had a higher mortality rate resulting from cardiac causes (p = 0.04) (18) . Likewise, Oliveira et al (28) showed no difference in HRQoL between ChD (n = 77) and non-ChD (n = 31) pacemaker patients in the physical (p = 0.094) and mental (p = 0.51) domains of the SF-36. However, ChD pacemaker patients had worse scores in the chest discomfort (p = 0.030) and arrhythmia (p = 0.004) domains of the AQUAREL.…”
Section: Sousa Gr Et Al -Health-related Quality Of Life In Patients mentioning
confidence: 99%
“…10 One study reported that 72% of pacemaker recipients in a Brazilian cohort displayed seropositivity for T cruzi. 11 Seropositivity as high as 25% has been reported in Bolivian children 5 to 13 years of age. 12 Understanding the true prevalence of untreated symptomatic bradycardia can be difficult because of a paucity of clinical data.…”
Section: Scope Of the Epidemicmentioning
confidence: 99%